The Health Department's Strategy in Efforts to Reduce Stunting Rates in Medan City - Puan Inggit Umairoh Rambe; Zoraya Alfathin Rangkuti (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Stunting is a condition of growth failure in children caused by chronic malnutrition, especially in the first 1000 days of life, resulting in a child's height not being appropriate for their age.Medan City remains one of the loci for stunting prevention in North Sumatra among 15 regencies/cities.Therefore, the prevention and reduction of stunting rates become the responsibility of the Medan City government agencies, one of which is the Medan City Health Office.In the reduction of stunting at the Medan City Health Office, it is known that there are issues such as programs that have not been running smoothly and a lack of human resources at several community health centers in Medan City.The objective of this research is to describe the strategies of the Health Office in efforts to reduce stunting rates in Medan City.The research method used in this study is descriptive research with a qualitative approach.The research results indicate that the Health Office's strategy in efforts to reduce stunting rates in Medan City has been quite effective, as evidenced by the decrease in stunting rates in Medan City and the fulfillment of several indicators. For instance.